Urocortin 2 - a protective effect in hypertension? - Dzieza-Grudnik, A; Siga, O; Walczewska, J; Wizner, B; Wolkow, P P; Messerli, F H; Grodzicki, T (Journal of physiology and pharmacology : an official journal of the Polish Physiological Society, 2023)
Urocortin 2, an endogenous selective ligand for the corticotropin-releasing hormone receptor type 2, has been suggested to exert cardioprotective effects. We analyzed the possible relationship between the level of Ucn2 and specific indicators of cardiovascular risk factors in patients with untreated hypertension and in healthy subjects. Sixty seven subjects were recruited: 38 with newly diagnosed treatment-naive hypertension (with no pharmacological treatment - HT group) and 29 healthy subjects without hypertension (nHT group). We evaluated ambulatory blood pressure monitoring, Ucn2 levels and metabolic indices. Multivariable regression analyses were performed to assess the effects of gender, age, and Ucn2 levels on metabolic indices or blood pressure (BP) level. Log of Ucn2 levels were higher in healthy subjects than in hypertensive patients (2.44±0.7 versus 2.09±0.66, p<.05) and correlated inversely with 24-hour diastolic blood pressure, and both night-time systolic and diastolic blood pressure regardless of age and gender (R2=0.06; R2=0.06; R2=0.052; respectively). Furthermore, Ucn2 levels inversely correlated with cholesterol and low-density cholesterol (LDL) concentrations in healthy subjects only. Ucn2 was independently related to total cholesterol (but not to LDL) regardless of age, gender and the presence of hypertension (R2=0.18). However, we did not find any relationship between urocortin 2, body mass index or waist-hip ratio as well as parameters of glucose metabolism. Our data indicates that higher levels of urocortin 2 are related to more favorable lipid profiles and lower blood pressure.